PATHOPHYSIOLOGY, TYPES, ITS MEDIATORS & TREATMENT STRATEGIES OF ALZHEIMER’S DISEASE: A SHORT REVIEW - Singh, Puneet; Sharma, Yogesh; Sharma, Ashutosh (Journal of Biomedical and Pharmaceutical Research, 2021)
Cognition in an extensive sense means information dispensation. It denotes a relatively high level of processing of definite information including thinking, memory, perception, incentive, skilled arrangements and language. Learning is the most attribute attributes of the man and also of higher animals. Learning is definite as the skill to alter behavior on the basis of understanding. We know that some reminiscences last for only a few seconds, whereas others last for hours, days, months or year. Dementia is generally defined as the loss of logical abilities (medically called cognitive dysfunction) of sufficient capacity to interfere with social or occupational functioning.  People with DLB have some of the symptoms common in Alzheimer’s, but are more likely than people with Alzheimer’s to have initial or early symptoms such as sleep disturbances, well-formed visual hallucinations, and muscle rigidity or other parkinsonian movement features. The signature lesions in AD are neuritic plaques and neurofibrillary tangles (NFTs) to be found in the cortical areas and medial temporal lobe structures of the brain.Keywords: Alzheimer, Neurofibrillary tangles, Neuritic plaques, Dementia, Temporal lobe